Testing for fault activity at Yucca Mountain, Nevada, using independent GPS results from the BARGEN network - Hill, Emma M. (2012)
Data from BARGEN GPS stations around Yucca Mountain (YM) have been independently processed using GIPSY-OASIS and GAMIT/GLOBK. The RMS velocity differences between these solutions is 0.06 mm/yr ( east component) and 0.10 mm/yr ( north), indicating an ability to resolve tectonic signals > 0.3 mm/yr with high confidence. Inversion of GPS station velocities for Eastern California Shear Zone (ECSZ) fault parameters produces an unreasonably deep locking depth of similar to 30 km for the Death Valley-Furnace Creek fault system, contradicting seismological evidence. The GPS cluster locally west of YM observes a strain rate of 17.0 +/- 1.8 ns/yr, marginally higher than our ECSZ model predicts (13.9 +/- 0.7 ns/yr). Significantly, the cluster to the east observes 22.3 +/- 2.1 ns/yr, which is 6.2 sigma higher than the model (8.6 +/- 0.7 ns/yr), suggesting that additional sources of strain more local to YM (< 30 km) are currently active, collectively accumulating > 0.7 mm/yr.